Accurately Controlled Delivery of Temozolomide by Biocompatible UiO-66-NH2 Through Ultrasound to Enhance the Antitumor Efficacy and Attenuate the Toxicity for Treatment of Malignant Glioma - Wan Z (Dove Medical Press, 2021)
Zhiping Wan,1,* Chunlin Li,2,* Jinmao Gu,1,* Jun Qian,1 Junle Zhu,1 Jiaqi Wang,2 Yinwen Li,2 Jiahao Jiang,1 Huairui Chen,1 Chun Luo1 1Department of Neurosurgery, Tongji Hospital, School of Medicine, Tongji University, Shanghai, 200092, People’s Republic of China; 2Trauma Center, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chun Luo; Huairui Chen Email boyluochun@126.com; chen13761626536@163.comBackground: Glioma is the most common and malignant primary brain tumour in adults and has a dismal prognosis. Temozolomide (TMZ) is the only clinical first-line chemotherapy drug for malignant glioma up to present. Due to poor aqueous solubility and toxic effects, TMZ is still inefficient and limited for clinical glioma treatment.Methods: UiO-66-NH2 nanoparticle is a zirconium-based framework, constructed by Zr and 2-amino-1,4-benzenedicarboxylic acid (BDC-NH2) with octahedral microporous structure, which can be decomposed by the body into an ionic form to discharge. We prepared the nanoscale metal-organic framework (MOF) of UiO-66-NH2 to load TMZ for therapy of malignant glioma, TMZ is released from UiO-66-NH2 through a porous structure. The ultrasound accelerates its porous percolation and promotes the rapid dissolution of TMZ through low-frequency oscillations and cavitation effect. The biological safety and antitumor efficacy were evaluated both in vitro and in vivo.Results: The prepared TMZ@MOF exhibited excellent biocompatibility and biosafety due to minimal drug leakage without ultrasound intervention. We further used the flank model of glioblastoma to verify the in vivo therapeutic effect. TMZ@UiO-66-NH2 nanocomposites could be well delivered to the tumour tissue, which led to local enrichment of the TMZ concentration. Furthermore, TMZ@UiO-66-NH2 nanocomposites under ultrasound demonstrated much more efficient inhibition for tumor growth than TMZ@UiO-66-NH2 nanocomposites and TMZ alone. Meanwhile, the bone marrow suppression side effects of TMZ were significantly reduced by TMZ@UiO-66-NH2 nanocomposites.Conclusion: In this work, TMZ@UiO-66-NH2 nanocomposites with ultrasound mediation could effectively improve the killing effect of malignant glioma and decrease TMZ-induced toxicity in normal tissues, demonstrating great potential for the delivery of TMZ in the clinical treatment of malignant gliomas.Keywords: MOF, TMZ, ultrasound glioma